Lower ghrelin levels does not impact the metabolic benefit induced by Roux-en-Y gastric bypass - Liang, Yuan; Yu, Ruili; He, Rui; Sun, Lijun; Luo, Chao; Feng, Lu; Chen, Hong; Yin, Yue; Zhang, Weizhen (Frontiers in Endocrinology, 2022)
Objective Roux-en-Y gastric bypass is an effective intervention for metabolic disorder. We aim to elucidate whether ghrelin contributes to weight reduction, and glycemic and lipid control after Roux-en-Y gastric bypass (RYGB). Design Four-week-old WT and Ghrl-TSC1-/- mice were fed high fat diet for 12 weeks before surgery, and continued to be on the same diet for 3 weeks after surgery. Body weight, food intake, glycemic and lipid metabolism were analyzed before and after surgery. Results Gastric and circulating ghrelin was significantly increased in mice with RYGB surgery. Hypoghrelinemia elicited by deletion of TSC1 to activate mTOR signaling in gastric X/A like cells demonstrated no effect on weight reduction, glycemic and lipid control induced by Roux-en-Y gastric bypass surgery. Conclusion Lower ghrelin levels does not impact the metabolic benefit induced by Roux-en-Y gastric bypass.